Thermal analysis and fuel economy benefits of cylinder deactivation on a 1.0l spark ignition engine - Bech, Alexander (2018)
The deactivation of a cylinder on a 1.0litre three cylinder turbocharged gasoline engine has been investigated providing novel information on thermal and fuel consumption effects associated with the technology. This comes in light of providing solutions to reduce fuel consumption and CO2 emissions resulting from internal combustion engines. The investigation has been carried out through the PROgram for Modelling of Engine Thermal Systems (PROMETS). A version of PROMETS was extensively developed to characterise a commercially produced TCE not fitted with cylinder deactivation technology. Developments include an improved gas-side heat transfer expression to account for increased heat transfer to coolant due to the addition of an integrated exhaust manifold; addition of an expression to represent natural convection to model heating of quiescent coolant in the block; and a method to estimate the boosted intake manifold pressure past the throttle due to turbocharging on a gasoline engine. The 0-D approach used in this thesis compared to higher resolution computational tools has allowed for thermal and performance predictions to be made within a couple of minutes compared to several hours or days. In effect, PROMETS has been a time and cost effective tool during the development stages of a prototype engine. The PROMETS model indicated that no adverse changes in engine thermal behaviour arose with cylinder deactivation. The largest temperature change of < 400 occurs in the exhaust valve lower stem for the deactivated cylinder. Temperature changes in other components throughout the engine are an order of magnitude smaller. Although the largest temperature differences between the deactivated and firing cylinders were found to be in the range of < 70 , these remain within normal engine operating temperatures of < 100 . Also, by on-setting deactivation past an oil temperature of 40 , warm-up times were marginally extended compared to operation on all cylinders from key-on. Experimental inputs representing changes in engine gross indicated thermal efficiency and the work loss associated with the motoring of a piston complemented modelling work in predicting fuel consumption changes due to deactivation. Reductions in pumping losses account for the majority of the fuel consumption benefit associated with deactivating a cylinder. The main limitation in the employment of cylinder deactivation stems from the deterioration in the gross indicated thermal efficiency. Modelled results show that fuel consumption improvements are highest on low and part load operation envelopes. As such over the NEDC and FTP-75 benefits are in the range of 3.5%. Applying the technology over dynamically loaded cycles such as the WLTC and ARTEMIS, results in benefits of less than 1.6%. Further to modelling work on cylinder deactivation, experimental work has been carried out with the aim of allowing any engine size to be tested to cover transient drive cycles for future research.